Development of Reduce Graphene Oxide (rGO)/ Polypyrrole Composite towards Potential Application of CO2 Gas Sensor (International Journal of Scientific Research in Science and Technology, 2025)
Ppy and Ppy/rGO composites were synthesized using a one-step in-situ oxidation polymerization process. The synthesis involves incorporating reduced graphene oxide (rGO) into the Ppy matrix to improve its sensing properties. Composites were characterized using XRD and FTIR. Response time and the recovery time of sensors were estimated by the static response. The response time of pure Ppy substrate is found to be more than that of Ppy/rGO 10%. Recovery time of Ppy is more as compared to shorter recovery time of Ppy/rGO 10 % i.e 54s. As the recovery time of Ppy/rGO is very less, the active layer can be used as a potential CO2 sensor for carbon dioxide gas sensing and monitoring. Thus, study demonstrates the potential of using Ppy/rGO composites in practical gas-sensing devices, especially for detecting CO2. The enhanced performance attributed to the rGO doping makes it a valuable approach for improving sensor technologies.